Assessment of knowledge of hand washing among health care providers in Juba Teaching Hospital, South Sudan - Charles O.C. Langoya; Nigel J. Fuller (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
Background: Nosocomial infections increase mortality and morbidity although adherence to simple hand washing procedures is suggested to reduce these. Purpose: To assess knowledge of hand washing among health care providers in Juba Teaching Hospital (JTH) in South Sudan and establish associations with demographic, professional and clinical factors. Methods: A total of204 participants (126 men and 78 women) enrolled in a cross-sectional survey. Demographic, professional and clinical factors and knowledge scores (correct answers from 25 questions) were obtained and compared using t-test, ANOVA, chi-square test and correlation coefficient (r) as appropriate. Results: Participants were aged 29.8 (SD, 5.4) years. The majority (62.7%) had no hand washing training within the last three years. Inconsistent answers regarding knowledge were obtained with a mean knowledge score 15.02 (SD, 2.73). Age was associated with hand hygiene training as those untrained (mean 30.6, SD 5.5 years) were significantly older than those trained (28.5, SD 4.9 years); t = 2.60; p < 0.01. Age was also associated with knowledge score (r = -0.14, p = 0.048). However, there was no significant association between hand hygiene training and knowledge score (trained, 15.39, SD 3.07; untrained, 14.80, SD 2.48); t = 1.41; p = 0.15. Conclusion: Insufficient and inconsistent knowledge of hand hygiene was evident and younger workers were more likely to have attended recent hand hygiene training and had better knowledge of hygienic patient care than older health care workers in JTH.